Ballast Water Control: Issues & Recommendations for Protecting the United States' Shared Pacific Coastline - Rebecca M. Thibault (Washington University Global Studies Law Review, 2011)
The Article presents information on the ballast water discharge with reference to the pacific coastal at the U.S. The ballast water discharge that are used for controlling invasive species lack the international standards and this effects the public health and economic of the country. Information on the survey regarding the water control conducted by the U.S. and a specialized agency of the United Nations called the International Maritime Organization is also presented.
Keywords: Standards; Discharge of ballast water; Introduced organisms; Public health; International Maritime Organization; United Nations